Dual gated PET/CT imaging of heart - Kokki, Tommi (fi=Turun yliopisto|en=University of Turku|, 2021)
Coronary artery disease (CAD) resulting from atherosclerotic arterial changes, plaques, is a progressive process, which can be asymptomatic for many years. Asymptomatic CAD can cause a heart attack that leads to sudden death if the vulnerable coronary plaque ruptures and causes artery occlusion. The plaque inflammation plays an important role in the rupture susceptibility. Reliable anticipation of rupture is still clinically impossible for a single patient. Detection of the vulnerable coronary plaques before clinical signs remains a significant scientific challenge where positron emission tomography (PET) can play an important role. The aim of this dissertation was to find out whether a small, coronary plaque size, heart structures could be detected by a clinically available positron emission tomography and computed tomography (PET/CT) hybrid camera in realistically moving cardiac phantoms, a minipig model, and patients with CAD. Due to cardiac motions accurate detection of small heart structures are known to be problematic in PET imaging. Due to absence of commercial application at the beginning of the study, new dual gating method for cardiac PET imaging was developed and programmed that takes into account both contraction and respiratory induced cardiac motions. Cardiac phantom PET studies showed that small, active and moving plaques can be distinguished from myocardium activity and the gating methods improved the detection sensitivity and resolution of the plaques. In minipig and CAD patient cardiac PET studies small structures of myocardium and coronary arteries was detected more sensitive and accurately when using dual gating method than manufacturer gating methods. In cardiac patient PET study respiratory induced cardiac motions were shown to be linearly dependent with spirometry-measured respiratory volumes. Standard 3-lead electrocardiogram (ECG) measurement can be filtered by anesthesia monitor to detect lung impedance signal. In cardiac patient PET study this lung impedance signal were applied for respiratory gating. In this study was observed that the 3-lead ECG derived impedance signal gating method detects respiratory induced cardiac motion in PET as well as other externally used respiratory gating methods. In summary, the dual gated cardiac PET method is more sensitive and accurate to detect small cardiac structures, as coronary vessel wall pathology, than the commercial methods used in the study.

Sydämen kaksoisliiketahdistettu PET/CT kuvantaminen Ateroskleroottisten valtimomuutosten, plakkien, seurauksena asteittain kehittyvä sepelvaltimotauti voi olla vuosia oireeton. Oireeton sepelvaltimotauti voi aiheuttaa äkkikuolemaan johtavan sydäninfarktin, mikäli sepelvaltimon seinämäplakin repeytymisestä aiheutuu verisuonen tukkiva hyytymä. Tutkimuksissa on osoitettu, että plakin tulehduksella on merkittävä rooli repeytymisalttiudelle. Repeytymisen luotettava ennakointi on yksittäisen potilaan kohdalla edelleen kliinisesti mahdotonta. Tulehtuneiden ja repeytymisalttiiden sepelvaltimoplakkien toteaminen ennen kliinisiä oireita on edelleen merkittävä tieteellinen haaste, missä positroniemissiotomografia (PET) kuvantamisella voi olla merkittävä rooli. Väitöskirjan tavoitteena oli selvittää, voidaanko kliinisessä käytössä olevalla positroniemissiotomografia ja tietokonetomografia (PET/TT) yhdistelmäkameralla havaita pieniä, sepelvaltimoplakkien kokoisia, sydämen rakenteita koneellisesti toimivissa todenmukaisissa sydänmalleissa, eläinmallissa ja sepelvaltimotautia sairastavilla potilailla. Sydämen pienten rakenteiden tarkka havaitseminen PET/TTkameroilla on haasteellista sydämen liikkumisen vuoksi. Tutkimuksessa kehitettiin ja ohjelmoitiin uusi sydämen PET-kuvantamisen liiketahdistusmenetelmä, joka ottaa huomioon sekä sydämen supistusliikkeen että hengitysliikkeen vaikutuksen sydämen PET kuvantamissa. Koneellisilla sydänmalleilla osoitettiin, että PET on riittävän herkkä havaitsemaan pieniä ja liikkuvia radioaktiivisia ”sepelvaltimoplakkeja”, ja että liiketahdistusmenetelmät parantavat plakkien havaitsemisherkkyyttä ja tarkkuutta. Eläinmallissa ja sepelvaltimotautipotilailla kaksoisliiketahdistusmenetelmän herkkyys ja tarkkuus havaita pieniä sydänlihaksen ja sepelvaltimoiden rakenteita todettiin kaupallisia tahdistusmenetelmiä paremmaksi. Potilastutkimuksissa todettiin hengityksen aiheuttama sydämen liike PET-kuvissa lineaarisesti riippuvaiseksi spirometrialla mitattujen hengitystilavuuksien kanssa. Tavallisesta 3-johtoisesta sydänsähkökäyrästä voidaan anestesiamonitorin avulla suodattaa keuhkojen impedanssisignaalia. Hengitysliikkeen aiheuttama potilaiden sydämen liike PETkuvissa havaittiin yhtä hyvin käyttämällä tätä keuhkojen impedanssisignaalia kuin muita yleisesti käytettäviä ulkoisia hengitystahdistussignaaleja. Todetaan, että kaksoisliiketahdistettu sydämen PET-kuvantamismenetelmä on tutkimuksessa käytettyjä kaupallisia menetelmiä herkempi ja tarkempi havaitsemaan sydämen pieniä rakenteita sekä sepelvaltimon seinämän tulehdusplakkeja.